The Effect of Communication, Information, and Education (CIE) of Tuberculosis in Public Communities on the Awareness of Early Detection of Tuberculosis - Karyawanto Karyawanto; Budi Antoro; Febiya Ayu Weniar (Indonesian Journal of Global Health Research, 2023)
Tuberculosis (TB) is one of many infectious diseases that are still a public health problem worldwide. In 2019, WHO declared a global TB disease emergency because, in most countries, TB is getting out of control, especially in developing countries. Media use in health education should include things that support TB control programs, especially MDR-TB. This study aimed to determine the effect of tuberculosis communication, information, and education (CIE) in the community on awareness of early detection of tuberculosis in the community at the Kedondong sub-district health center, Pesawaran district, in 2021. The type of research used in this research is the Quasi Experiment. This type of experimental research makes observations twice, where before (pre-test) and after (post-test). The population in this study is the community at the Kedondong Health Center, Kedondong District, Pesawaran Regency. Three hundred sixty samples of respondents were taken by purposive sampling technique. Data were collected by questionnaire and analyzed by chi-square statistical test. he results of the validity and reliability tests revealed that there was an effect of IEC on awareness of early detection of tuberculosis. The results showed that the median value before giving CIE was 31, and the median value after giving CIE was 40. There was a clear difference in the average between before and after being given the CIE intervention. The statistical test obtained a p-value of 0.00, where the p-value <0.05 means that giving CIE affects awareness of early tuberculosis detection. Activities like this can be carried out on an ongoing basis to monitor medication adherence and PHBS habits in preventing the transmission of TB disease.